El vídeo educativo y el desarrollo de la capacidad de autoestima en estudiantes de la institución educativa “Liceo Trujillo” - Trujillo - Chavez Lezama, Sandra Elizabeth (2019)
The objective of the present investigation is determining the influence of the educational video in the development of the capacity of self-esteem in III's students the Educational Institution's cycle of primary school Lyceum Trujillo. The population was composed of all the students of the third cycle of primary school (n= 378). The sample was composed by (n= 36) students. The selection of the sample did by means of sampling probabilistic no itself, applying the investigator's intentional opinion. Data were picked up by means of a test._x000D_ The results came under a system by means of statistical pictures and for hypothesis testing student's T for independent sample applied the estadígrafo itself. Findings were the following: 1) The high-quality level of self-esteem, dimensions: physics self-esteem, general, academic, emotional and the relations is bad (42.7 %) on the average) prone to deficient according to the pretest. 2) The high-quality level of self-esteem, dimensions: physics self-esteem, general, academic, emotional and the relations is good (45.3 % on the average) prone to very good according to the after test. 3) The educational video like didactic resource, in the development of the capacity of self-esteem of the students of primary education significantly.